Geopolitical Challenges and Constraints in Paradiplomacy: The Sister City Cooperation between Jember Regency and the City of Thessaloniki - Abhista Athaviannas Bachtiar; Hamdan Nafiatur Rosyida; Azza Bimantara (Program Studi Ilmu Pemerintahan, FISIP - Universitas Halu Oleo, 2026)
Jember Regency had the opportunity to establish a sister-city partnership with the City of Thessaloniki, Greece, encompassing potential cooperation in the blue economy, green technology, and the exchange of experience in waste management. However, the outbreak of COVID-19 generated post-pandemic impacts that resulted in the cancellation of the planned cooperation between the two parties. This study employs the concepts of paradiplomacy and geopolitical risk in city diplomacy. The research method used is a qualitative descriptive case study, aimed at explaining the challenges and obstacles in the prospective sister-city cooperation between Jember Regency and the City of Thessaloniki. Data were collected through library research and interviews with several parties directly involved in the proposed cooperation. The findings indicate that the discontinuation of the cooperation was attributable to geopolitical risk, namely the COVID-19 pandemic, which produced post-pandemic effects and led to policy changes, prompting both parties to cancel the planned partnership. This study seeks to explain the case from the perspective of geopolitical risk in city diplomacy and to contribute a renewed understanding of geopolitical risk factors within city diplomacy.